The Significant Contribution of Indonesian Human Capital to the Economic Growth - Tobing, C. Ruth Elisabeth (International Research Journal of Business Studies, 2011)
This study examines the contribution of human capital to Indonesia’s productivity. The result of this study reveals a significant contribution of human capital as shown in the model which is using highest weighted of primary and secondary level of education. The most significant result found in the model using secondary level as the highest weighted of human capital. In contrast, there is no significant contribution of human capital using proportional weighted between education levels. This suggests that improvement in knowledge, adoption of technology and skill in the primary and secondary education meet the demand of industries in Indonesia. This study uses a time series regression to analyze data 1985-2010.